Character Design to Support Socialization of The Urban Forest Existence in Jakarta - Tunjung Riyadi; Ardiyan Ardiyan; Veronica Wijayanti (Bina Nusantara University, 2016)
The purpose of this study was to help the campaign of related messages and invites the public to participate in caring for the existence of the urban forest in Jakarta. Method design of this study was through the stages of observation in the form of search data by observation, literature reference, and then elaboration of mapping problem analysis, synthesis in the form of search and define the character core visual as the main idea. It was also supported by the theories related to the visual character animation, communication, semiotics, and gestalt. The result is character design with a variety of functions such mascot, campaign logo, and public service advertising. In conclusion, through this character design is expected to communicate messages easier about the existence of urban forest in Jakarta.